Targeting the FSH/FSHR axis in ovarian cancer: advanced treatment using nanotechnology and immunotherapy - Feng, Fuqing; Liu, Tianhang; Hou, Xiaoman; Lin, Xueyan; Zhou, Susu; Tian, Yongjie; Qi, Xiaoyi (Frontiers in Endocrinology, 2024)
Ovarian cancer (OC) is the gynecological malignancy with the poorest prognosis. Surgery and chemotherapy are the primary therapies for OC; however, patients often experience recurrence. Given the intimate interaction between OC cells and the tumor microenvironment (TME), it is imperative to devise treatments that target both tumor cells and TME components. Recently, follicle-stimulating hormone (FSH) levels in the blood have been shown to correlate with poorer prognosis in individuals with OC. Ovarian carcinoma cells express FSH receptors (FSHRs). Thus, FSH is an important target in the development of novel therapeutic agents. Here, we review the effects of FSH on normal physiology, including the reproductive, skeletal, cardiac, and fat metabolic systems. Importantly, this review outlines the role and mechanism of the FSH/FSHR axis in the proliferation, survival, and metastasis of OC, providing theoretical support for the targeted FSHR treatment of OC. Current progress in targeting FSHR for OC, including the recent application of nanotechnology and immunotherapy, is presented. Finally, we discuss prospects and future directions of targeted FSHR therapy in OC.